CATUR STEM: Buku Panduan bagi Guru Kimia untuk Menyusun RPP Berbasis STEM - Muhammad Isnaini; Ratna Farwati; Kartika Metafisika (Orbital: Jurnal Pendidikan Kimia, 2023)
There are not many detailed explanations on how to design STEM learning in chemistry lesson scope. This has made researchers and chemistry teachers not understand about its application in the classroom. Therefore, this study aims to develop a guidebook containing theories on how to design STEM learning. This research used Design and Development Research with these stages being carried out, namely (1) analysis of STEM concepts and lesson plans, (2) design of the CATUR STEM outline, (3) development of the contents of the CATUR STEM guidebook, and (4) assessment which includes validation of guidebook content. This guidebook has been declared very valid without revision by 12 validators involved with a validity value of 3.74 (out of a maximum score of 4.00). This guidebook contains information about STEM learning using modification of Engineering Design Process (EDP), how to create lesson plans based on Merdeka Belajar policy and STEM-EDP learning, and a collection of examples of STEM-EDP learning lesson plans. It is highly expected that this guidebook will later be tested to teachers of early childhood education programs, elementary schools, junior high school as an attempt to strengthen the theory of the STEM learning model.